Exploring the Food Expenditure Patterns of College Students - Joel Fatto Amoakon; Godfrey Ejimakor; Deric Hardy (European Scientific Journal, ESJ, 2017)
This study explored the food expenditure patterns of college students. Information on monthly food expenditures and income from a sample of students was used to estimate the proportion of income that the average student spends on food and analyze the Engel relation between food expenditures and income. The average college student was found to spend about 30 percent of income on food. The estimated marginal share is 0.076. These findings indicate that food and related establishments that sell mostly to college students will receive very little of any potential increases in student income. However, increases in student income may be a boon for businesses that sell non-food items.